Innate IFN-γ-Producing Cells Developing in the Absence of IL-2 Receptor Common γ-Chain - Resende, M (2017)
IFN-γ is known to be predominantly produced by lymphoid cells such as certain subsets of T cells, NK cells, and other group 1 innate lymphoid cells. In this study, we used IFN-γ reporter mouse models to search for additional cells capable of secreting this cytokine. We identified a novel and rare population of nonconventional IFN-γ-producing cells of hematopoietic origin that were characterized by the expression of Thy1.2 and the lack of lymphoid, myeloid, and NK lineage markers. The expression of IFN-γ by this population was higher in the liver and lower in the spleen. Furthermore, these cells were present in mice lacking both the Rag2 and the common γ-chain (γc) genes (Rag2-/-γc-/-), indicating their innate nature and their γc cytokine independence. Rag2-/-γc-/- mice are as resistant to Mycobacterium avium as Rag2-/- mice, whereas Rag2-/- mice lacking IFN-γ are more susceptible than either Rag2-/- or Rag2-/-γc-/- These lineage-negative CD45+/Thy1.2+ cells are found within the mycobacterially induced granulomatous structure in the livers of infected Rag2-/-γc-/- animals and are adjacent to macrophages that expressed inducible NO synthase, suggesting a potential protective role for these IFN-γ-producing cells. Accordingly, Thy1.2-specific mAb administration to infected Rag2-/-γc-/- animals increased M. avium growth in the liver. Overall, our results demonstrate that a population of Thy1.2+ non-NK innate-like cells present in the liver expresses IFN-γ and can confer protection against M. avium infection in immunocompromised mice.